Non-standard employment, working time arrangements, establishment entry and exit - Jochen Späth (Institut für Angewandte Wirtschaftsforschung (IAW), 2013)
This paper addresses the issue if and to what extent young firms differ from incumbents regarding the use of non-standard employment, trust-based working time arrangements and overtime hours in the light of the qualitative changes of employment structures that are taking place in industrialized countries, such as rising shares of non-standard employment and borders between work and private life that become increasingly blurred. Based on a microeconometric analysis of the IAB Establishment Panel, a representative survey of about 16,000 employers in Germany, we find that young establishments rely significantly more often on limited contracts and freelance work than incumbent businesses in order to hedge the higher risks and uncertainties of young firms. Likewise, trust-based working time arrangements and overtime hours are more an issue in young than in incumbent firms, indicating a higher level of subjectivated work in young firms. Additionally, we provide basic evidence that these differences are not purely transitory but on the contrary rather stable as the firms grow older, which makes young firms contribute a substantial part to the ongoing qualitative changes of employment structures.
Keywords: L26; J23; D22; 330; start-ups; trust-based working hours; overtime; team work; job quality; non-standard employment